TI_GERICHTE 90.2015.73 vom 21. Oktober 2016 , Vincolo AP-EP per la realizzazione di un ecocentro e di un'area di compostaggio - TI Tribunale d'appello (2016)
Vincolo AP-EP per la realizzazione di un ecocentro e di un'area di compostaggio